Epistles and Their Use as Documentary Sources in Historia de Japam (1585-1593) by Jesuit Luís Fróis: Comparative Analysis of an Episode - Hoyos Hattori, Paula (2017)
This paper analyzes two documents from the Jesuit mission to Japan, both written by Luís Fróis (1532-1597). They discuss the same topic: the conversion to Christianity of a young nobleman from Bungo (Kyushu) in 1577. One is an epistle and the other deals with historic issues. The comparison reveals the peculiarities of each genre, in line with the norms of the Society of Jesus. The paper concludes that epistles were considered to strengthen spiritual and identity links, as a result of which they were widely disseminated during the 16th century.